Analisis Prosedur Hukum Acara Perdata Terkait Sengketa Hak Atas Tanah: (Tumpang Tindih Sertifikat) - Violla Evarista; Kristanto Kristanto; Vinanda Langgeng Kencana; Riyan Ardiansyah; I Komang Agus Tri Wismantara (Prosiding Seminar Nasional Ilmu Hukum, 2026)
Land rights disputes arising from overlapping land certificates remain a complex agrarian law issue frequently encountered in Indonesia. This phenomenon reflects weaknesses in the land administration system, particularly in data collection, land measurement, and certificate issuance. Such disputes create conflicts, legal uncertainty, and reduced public trust in the land registration system. In practice, these disputes are generally resolved through civil litigation procedures in the District Court. This study aims to comprehensively analyze civil procedural law in resolving land rights disputes involving overlapping certificates and to examine the evidentiary strength of land certificates in judicial proceedings. This research employs a normative legal method using statutory and conceptual approaches, supported by primary and secondary legal materials. The findings indicate that dispute resolution begins with the filing of a lawsuit, followed by mediation, court examination, and the evidentiary process as the most crucial stage in determining lawful ownership. Land certificates serve as strong evidence; however, they are not absolute, as they may be challenged if administrative or substantive legal defects are identified. Judges play a central role in assessing certificate validity by considering land history, physical possession, good faith, and compliance with legal procedures. Nevertheless, the effectiveness of dispute resolution still requires improvement through better land administration, enhanced data accuracy, and stronger institutional integration.